Low bone mineral density is present in newly diagnosed paediatric systemic lupus erythematosus patients. Issue 11 (13th September 2011) - Lim, Siok Hoon Lily; Benseler, Susanne M; Tyrrell, Pascal N; Charron, Martin; Harvey, Elizabeth; Hebert, Diane; Silverman, Earl D
Abstract : Objectives: The objectives of this study were to (1) determine the prevalence of low bone mineral density (BMD) in a large prospective cohort of newly diagnosed patients with paediatric systemic lupus erythematosus (pSLE) and (2) identify risk factors associated with low BMD. Methods: Single-centre cohort study of 80 children and adolescents who underwent a dual-energy x-ray absorptiometry within 3 months of diagnosis. Low lumbar spine (LS) BMD was defined as z score ≤−2.0. BMD was correlated with baseline demographic, clinical and laboratory markers of disease activity and biochemical markers of bone health. Risk factors of BMD were evaluated with univariable and multivariable linear and logistic regression analyses. Results: Low BMD at any site was found in 15% of newly diagnosed pSLE patients. LS BMD was associated with body mass index (BMI) z score and corrected calcium (r 2 =0.31, p<0.0001). Hip BMD was associated with BMI z score and intact parathyroid hormone (iPTH) (r 2 =0.26, p=0.002). Higher BMI z score was protective against low BMD at any site (OR 0.35). Conclusions: One in six newly diagnosed pSLE patients had low BMD (at any site). Low BMI z score, low calcium and high iPTH identified children at risk for low BMD at diagnosis of pSLE.